The last mapmaker - Soontornvat, Christina (Candlewick Press, 2022)
As the Mangkon royal navy Master Mapmaker's apprentice, twelve-year-old Sai keeps her lowly born status a secret. If anyone found out her father is a conman from the Fens, she'd lose her position. Though, that's likely to happen anyway, as her thirteenth birthday is approaching and that's when all high-born receive a gold bracelet denoting their lineage. She cheats destiny once again when her master, Paiyoon invites her on a sanctioned trip to explore a southern continent. But the voyage comes with its own set of dangers, including rumored dragons, and Sai will have to decide what price she is willing to pay for a better future.